Prevalence of RV dysfunction in patients under cardiotoxic chemoterapy: a preliminary analysis. (3rd October 2022) - Maltes, S; Rocha, B M L; Cunha, G J L; Paiva, M S; Vasques, A C; Freitas, P; Guerreiro, S; Marta, L; Abecasis, J; Regina, R; Andrade, M J; Aguiar, C T; et al.
Abstract: Background: Chemotherapy-induced cardiotoxicity is a serious complication often leading to heart failure. While the left ventricle (LV) has been thoroughly implicated in this process, data is scarce on right ventricular (RV) function following cardiotoxic chemotherapies. Our goal was to determine the prevalence and clinical significance of RV dysfunction in a cohort of patients who had received these drugs. Methodology: Single-center retrospective study of cancer patients performing 2D transthoracic echocardiogram between January 2020 and December 2021. Those previously exposed to anthracyclines and/or anti-HER2 agents (≥6 months prior to echocardiogram) were included. Patients with known coronary artery disease or cardiomyopathy were excluded. LV function was assessed through LV ejection fraction (LVEF) and global longitudinal strain (GLS). LV cardiotoxicity was defined as per 2020 ESMO guidelines. RV function was considered abnormal if the following criteria were met: tricuspid annular plane systolic excursion (TAPSE) <17 mm, peak systolic velocity of the tricuspid annulus by pulsed wave TDI (S'VD) <12 cm/s, fraction area change (FAC) <35% and mean free wall longitudinal strain (FWLS) >−20%. Results: Forty patients were included (58±13 years; 95% female; 93% with breast cancer; 30%, 20% and 50% previously treated with anthracyclines, anti-HER2 or both, respectively). Mean LVEF and GLS were 56±7% and −17±3%. Overall, 13 patients had current LV cardiotoxicity. RV dysfunction was documented in 15 (38%) patients (7 [18%] with isolated RV dysfunction), most often detected through FWLS (14 [35%], 7 [18%], 6 [15%] and 5 [13%] patients with abnormal FWLS, TAPSE, FAC and S'VD, respectively) – Figure 1. Seven patients (18%) and one patient (3%) had ≥2 and ≥3 abnormal RV parameters. Those with RV dysfunction were more often symptomatic (NYHA class ≥2: 53% vs. 16%; p=0.013), had higher NT-proBNP levels (516 [204–2400] vs. 66 [46–191] pg/mL; p=0.003) and most often had LV cardiotoxicity (62% vs. 26%, p=0.029); pulmonary artery systolic pressures were similar between both groups. Conclusion: In our cohort of patients treated with cardiotoxic anti-neoplastic drugs, RV dysfunction was observed in two out of every five patients, most often detected by RV 2D strain and associated with worse symptoms and higher NT-proBNP levels. This data suggests that RV cardiotoxicity may be common and clinically impactful in those under cardiotoxic chemotherapies. Funding Acknowledgement: Type of funding sources: None.